Combination of Anterior and Posterior Vaginal Mesh Implants and Delorme Procedure in a 94-year-old female with Pelvic Organ Prolapse - Hien Van Nguyen; Dung Thi Ngo; Dat Vinh Lieu; Tuan Thanh Tran (Nigerian Postgraduate Medical Journal)
Pelvic organ prolapse refers to the descent of pelvic floor organs resulting from the weakening of pelvic muscles, fascia and connective tissue. The overall prevalence of pelvic organ prolapse is approximately 41%, including bladder prolapse (25%–34%), uterine prolapse (4%–14%) and rectal prolapse (13%–19%). Various methods are currently employed to repair damaged structures and improve patient symptoms, consequently enhancing their quality of life. This report focuses on a 94-year-old female diagnosed with pelvic organ prolapse, specifically Grade 3 bladder prolapse, Grade 3 uterine prolapse and complete rectal prolapse. A comprehensive surgical treatment was carried out to repair the pelvic organs on all three levels (rectum, uterus and bladder) by combining the Delorme procedure with synthetic graft implants. The surgical outcomes were good, illustrating immediate improvement in symptoms without early complications. A multispeciality approach helps functionally repair pelvic organ prolapse while preserving structural integrity.